Effect of Integrated Care on Patients With Atrial Fibrillation: A Systematic Review of Randomized Controlled Trials - Li, Yi; Zhao, Wenjing; Huang, Jun; Zheng, Murui; Hu, Peng; Lu, Jiahai; Deng, Hai; Liu, Xudong (Frontiers in Cardiovascular Medicine, 2022)
Aims: The integrated management was evidenced to improve the hospitalization and its associated complications in patients with atrial fibrillation (AF), but the strategies of integrated care varied and results were inconsistent. This systematic review and meta-analysis aimed to evaluate the effect of integrated care on AF-related outcomes with comparison with usual care. Methods: PubMed, Embase, and Web of Science were searched for articles published until 10th January 2022. Eligible studies were randomized controlled trials to study the effect of integrated care on AF-related outcomes. Meta-analysis with a random-effect model was used to calculate risk ratio (RR) and 95% confidence interval (CI) by comparing the integrated care with usual care. Results: A total of five studies with 6,486 AF patients were selected. By synthesizing available data, integrated care effectively reduced the risk of all-cause mortality (RR = 0.54, 95% CI = 0.42 - 0.69), cardiovascular hospitalization (RR = 0.72, 95% CI = 0.55 - 0.94), and cardiovascular mortality (RR=0.52, 95% CI=0.36 - 0.78) when compared with usual care; however, there was no superior effect on preventing AF-related hospitalization (RR = 0.86, 95% CI = 0.72 - 1.02), cerebrovascular events (RR = 1.13, 95% CI = 0.75 - 1.70), and major bleeding (RR = 1.29, 95% CI = 0.86 - 1.94) when comparing integrated care with usual care. Conclusion: Integrated care can reduce the risk of all-cause mortality, cardiovascular mortality, and cardiovascular hospitalizations in AF patients compared with usual care, while the benefit was not observed in other outcomes.